Determining foot-ankle mechanism design by mapping the relationships among bones, joints, and ground reaction force - Bani Hashim, Ahmad Yusairi; Noor Azuan, Abu Osman; Wan Abas, Wan Abu Bakar (Global Engineers and Technologists Review, 2011)
This work investigates the following questions—why the bones and the joints are arranged in that way, why it is different from other primates, and how could it be imitated to develop a foot-ankle mechanism. Mathematical models were developed and were based on the relationship among the anatomy of bones and joints, the normalized ground reaction forces that acted on certain nodes on the footprint. Using the model, a custom design prosthetic foot was assembled. It was tested on a robot arm that simulated a walking gait. The stance phase cycle performed on the prototype, and the commercial feet were completed within approximately 1.08 seconds and 1.38 seconds, respectively. The techniques used, however, may require further studies because the prototype foot was not tested on patients. At this stage, the techniques are sufficient to justify that the prototype foot design should consist of an ankle-foot mechanism and a flexible keel. Therefore, proper mappings of bones and joints; and modeling of foot biomechanics is found useful in design and development of prosthetic feet activities.